PENGGUNAAN PROSHOW PRODUCER UNTUK MENINGKATKAN KETERAMPILAN MENULIS PARAGRAF PERSUASI PADA SISWA SMA MUHAMMADYAH 1 PONTIANAK - Ganeta, Ghina; Syambasril, Syambasril; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research was persuasive paragraph writing learning activity in 10th grade students of SMA Muhammadiyah had not showed maximum result. This research was qualitative research through two cycles. Each cycle consist of four steps which were planning, action, observation, reflection. The subjects of this research were Teacher and students. Data collecting tool in this research was test activity. Data analysis in this research was words description form. Based on the data analysis, it was concluded that the use of Proshow Producer Media could improve the result of persuasive paragraph writing learning. The use of Proshow Producer media gave benefits to the students in finding ideas words would be used in writing persuasive paragraph. In the cycle I, the studentsâ€™ average score was 72.64 with the lowest score was 55 and the highest was 80. After revising in cycle II, the studentsâ€™ average score reached 79.11 with the lowest score was 65 and the highest score was 90. The score improvement which was gained by students in each cycle proved that the use of Proshow Producer Media in persuasive paragraph writing was effective.Â Keywords: Proshow Producer Media, writing, persuasive paragraph